Plant based indian traditional medicine for neurodegenerative diseases - a novel Approach to treat alzheimer - PRASEETHA P K; PRATHEEBA; LATHIKA SOMASUNDARAM; G. SAKTHIVEL (International Journal of Pharma and Bio Sciences, 2016)
As per the earlier reports, the most prevalent disease of Alzheimer’s, a kind of dementia, affects approximately 24 million people worldwide. There may be many invisible reasons for the disease to be caused and the common evidences for the disease is due to a few reasons like aggregation of self-assembled fibrous proteins and variation in the level of Acetyl choline (ACh). Traditional Indian herbs which are rich in natural alkaloids and are an important source of acetyl-cholinesterase (AChE) which can restore the levels of acetylcholine. Bioactive compounds like Coumarins, flavonoids and other indirect sources from herbs can activate the complexes of the deadly disease, so that the derivatives work against the severity of the disease. The natural compounds derived from herbs can act as modulators and inhibitors for amyloid accumulation so that they can also suppress inflammation and neuronal cytotoxicity. These bioactive compounds have the advantage of being multi-targeted and hence are advantageous over the single target drugs in the treatment of such complex diseases. This review suggests the possibilities of using traditional Indian herbs which are a rich source of these compounds to effectively treat Alzheimer’s disease and hence has attracted attention towards research and development of the therapies.